Meditasi Buddhis: Sarana untuk Mencapai Kedamaian dan Pencerahan Batin - Bramantyo, Hastho (Jurnal Orientasi Baru, 2015)
Buddhist meditation is a means to self-examination and spiritual practices which mostly misunderstood both by Buddhist and non-Buddhist alike! Meditation is a thought of as a form of self-denial and escape from the harsh reality of life. It is not difficult to understand as people tend to associate the word of meditation to a man/women sitting cross legged, doing nothing, which suggest laziness and indifference toward life’s affairs. Contrary to the above misconception, Buddhist meditation is actually a way to attain spiritual prosperity and wisdom. The original term for Buddhist meditation is Bhavana, which means mental development. It consists of two modes of meditation, namely samatha/Samadhi, to attain mental quiescence, and vipassana/vipasyana, to achieve penetrative insight. Buddhist meditation is a powerful spiritual exercise to attain mental transformation and peace of mind. By utilizing the faculty of will power, concentration and sharp awareness, Buddhist meditation enabled the practitioners to realized tranquility, happiness and wisdom to the real nature of everything.